Do Ethical Climate and Trust Restrain Misidentification and Bullying in Organization? - Willson Gustiawan; Manh-Trung Phung (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Main Purpose – This study aims to examine the role of ethical climate and trust in restraining negative workplace behaviors, particularly organizational misidentification and workplace bullying, which remain relatively underexplored in ethical climate research. Method – This study employed a quantitative approach using survey data collected from 176 employees across various industries in Taiwan. The data were analyzed using reliability testing, confirmatory factor analysis, correlation analysis, hierarchical regression, and path analysis to examine the relationships and mediation effects among the variables. Main Findings – The results show tha ethical climate has a significant positive effect on trust and a significant negative effect on misidentification and workplace bullying. Employees perceiving a stronger ethical climate exhibit higher trust and lower negative workplace behaviors. Furthermore, the findings provide preliminary support for the mediating role of trust in the relationship between ethical climate and negative workplace behaviors. Theory and Practical Implications – This study advances the literature by combining ethical climate and trust in a single framework to explain underexplored negative workplace behaviors, such as organizational misidentification and bullying. Organizations can leverage ethical climate to foster trust among employees, thereby reducing negative workplace behaviors and promoting a healthier work environment. Novelty – This study integrates ethical climate and trust within a single mediation framework to explain the reduction of negative workplace behaviors.